Analisis Kinerja Keuangan Berdasarkan Net Profit Margin (NPM), Return On Equity (ROE), Return On Asset (ROA), Gross Profit Margin (GPM) dan Harga Saham Pada PT. MEGA Perintis Tbk - Iwan Eka Putra; Aulia Yunicha Harly; Azizah Septia Ningrum; Faizal Riza (Jurnal Development, 2024)
Financial performance is an important thing that needs to be known by internal and external parties. Because for internal parties it is used as a decision making tool to manage the company's finances well, while for external parties it is used as a decision making tool to carry out investment activities. For this reason, the author is interested in research with the title "Financial Performance Analysis Based on Net Profit Margin, Return on Equity, Return on Assets, Gross Profit Margin and Share Prices at PT. Mega Perintis Tbkâ€. This research is aims to determine the financial performance of PT. Mega Perintis Tbk, period 2018 to 2023 based on profitability ratios and share prices. Quantitative research method as a research technique that collects data through the use of research instruments and analyzes quantitative and statistical data to examine how PT. Mega Perintis Tbk's financial performance is influenced by profitability ratios and share prices between 2018 and 2023. The data analysis tool used in this research is financial ratio analysis in the form of profitability ratios and stock prices. The research results show that the profitability ratio of the Mega Perintis Tbk company from 2018 to 2023 is in a poor condition because the values of Net Profit Margin, Return On Equity, Return On Assets are below the industry average standard. However, the Mega Perintis Tbk company's Gross Profit Margin is in "good" condition because the Gross Profit Margin value is above the industry average standard.